Investigating prolonged jaundice in healthy breastfed infants- time to change current practice?. (24th May 2012) - Sampath, S; Puttha, R; Thomson, APJ; Thirumurugan, A
Abstract : Aim: To determine the yield of investigations routinely undertaken in healthy breastfed term infants with prolonged jaundice. Methods: Retrospective review of medical records of infants with prolonged jaundice referred during a 12-month period from August 2009 to July 2010. Inclusion criteria were (1) ≥ 37 weeks gestation at birth, (2) ≥ 14 days postnatal age (3) normal urine and stool culture. Infants with other clinical concerns were excluded. Microsoft excel was used for data analysis. Results: Forty-two infants were referred for prolonged jaundice. 37 met the study criteria; 5 infants were excluded (concerns with adequacy of feeding or weight gain in 4, type of milk feed not documented in 1). Conjugated bilirubin was normal in all infants. Full blood count was normal in 32 of 33 tested. In 1 infant spherocytosis was suspected but subsequently excluded. 34 had a normal Direct Coomb's test. Thyroid function test (TFT) was normal in 24 of 31 tested. 7 (22.5%) had transiently elevated Thyroid stimulating hormone levels. All abnormal TFTs spontaneously normalised over subsequent weeks. The universal newborn screening thyroid function test was normal in all infants. Urine reducing substances was negative in all 37 infants. 14 of 37 infants had urine tested with dipstix alone and none showed evidence of urinary tract infection (i.e. no nitrites or leucocytes). Of the remaining 23 infants, 14 had normal urine microscopy and culture, 9 had bacterial growth but no evidence of pyuria. Repeat urine microscopy and culture was however normal in these 9 infants. Conclusions: The yield of routinely undertaken laboratory investigations for prolonged jaundice was extremely low. If similar results can be demonstrated in a larger study, the threshold for investigations in these babies could be altered leading to reduced unnecessary investigations, whilst still not missing important diagnoses. This could also generate cost savings.